Pengaruh Model PjBL melalui Pendekatan TaRL terhadap Hasil Belajar Siswa Sekolah Dasar - Azzahroh, Fatimah; Windiyani, Tustiana; Hastuti, Sri (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
Education plays a role important for develop ability think critical and creative students, especially in the 21st century. However, the approach learning conventional teacher - oriented often hinder involvement active students, including in learning Knowledge Natural and Social Sciences (IPAS) topics water cycle. This research aims for analyze the influence of the Project Based Learning (PJBL) learning model through Teaching at the Right Level (TaRL) approach to results Study student school basic. Research quantitative with This pre- experimental design uses a one group pretest-posttest design on 23 students. class VD SDN Bangka 3 Bogor City. Data analyzed through normality test, N-Gain test, and paired sample t-test. The results showed that the average pretest score increased from 55.90 to 80.00 on the posttest, with N-Gain value of 0.58 (criteria medium). The t-test produces mark significance 0.000 < 0.05, indicating influence significant implementation of the PJBL learning model with approach TaRL to results Study students. In conclusion, the integration of PJBL and TaRL effective in increase results students learn science, at the same time give solution practical For accommodate difference ability student in learning based on project. This research contributes to the development of learning strategies. innovative, contextual and relevant for education base.